2015
DOI: 10.2217/mmt.15.30
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Markers in Melanoma

Abstract: Melanoma, one of the most virulent forms of human malignancy, is the primary cause of mortality from cancers arising from the skin. The prognosis of metastatic melanoma remains dismal despite targeted therapeutic regimens that exploit our growing understanding of cancer immunology and genetic mutations that drive oncogenic cell signaling pathways in cancer. Epigenetic mechanisms, including DNA methylation/demethylation, histone modifications and noncoding RNAs recently have been shown to play critical roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…It has been shown that a large group of genes are methylated in melanomas [54]. Among the TSGs that are reported to be hypermethylated most frequently in the process of melanoma development and progression are retinoic acid receptor-beta2 (RARbeta 2), RASSF1A, CDKN2A, PTEN genes [55].…”
Section: Melanomamentioning
confidence: 99%
“…It has been shown that a large group of genes are methylated in melanomas [54]. Among the TSGs that are reported to be hypermethylated most frequently in the process of melanoma development and progression are retinoic acid receptor-beta2 (RARbeta 2), RASSF1A, CDKN2A, PTEN genes [55].…”
Section: Melanomamentioning
confidence: 99%